Pendampingan Mahasiswa Universitas Mandiri dalam Kompetisi National Scientific Essay Competition - Permono Adi Putro; Asep Priatna; Aji Fauziana Ridwan (LPPI UMN AL WASHLIYAH, 2026)
The student mentoring program in the National Scientific Essay Competition (NSEC) is designed to improve scientific literacy, critical thinking skills, and presentation skills of students through five systematic stages. This study aims to describe the mentoring process, which includes searching for innovative ideas, essay writing, work registration, internal assessment, and final presentation preparation, as well as analyzing its impact on students' competitive readiness. Mentoring is carried out through an academic scaffolding approach, collaborative discussions, rubric-based evaluation, and mock presentations as the main strategies for strengthening competencies. The results show that two students from Universitas Mandiri successfully entered the NSEC TOP 10 Finalists, which indicates the effectiveness of the mentoring model in improving the quality of work, scientific communication skills, and student confidence. In addition, the direct experience in the final presentation provided practice-based learning that broadened the academic insights of the participants. These findings confirm that structured mentoring can be a relevant and applicable strategy in improving students' academic capacity and preparing them for national-level scientific competitions.